Management information systems - O’Brien, James A. (McGraw-Hill Irwin, 2006)
This new Seventh Edition is designed for business students who are or who will soon become business professionals in the fast changing business world of today. The goal of this text is to help business students learn how to use and manage information technologies to revitalize business processes, improve business decision making, and gain competitive advantage. Thus it places a major emphasis on up-to-date coverage of the essential role of Internet technologies in providing a platform for business, commerce, and collaboration processes among all business stakeholders in today’s networked enterprises and global markets. The benchmark text for the syllabus organized by technology, this text appraoches the material from a managerial perspective. O’Brien defines technology and then explains how companies use the technology to improve performance. Real world cases finalize and enhance the explanation